Archaeological method and theory : an encyclopedia - Ellis, Linda, Ed (Garland publishing , INC., 2000)
This Encyclopedia brings together the most recent scientific information on a collection of subjects that are too often - and inconveniently - treated in separate publications. It provides a survey of archaeological method and theory, as well as the application of physical and biological sciences in archaeological research. Every aspect of archaeological work is represented, from the discovery process to the ultimate disposition of materials. Thus the reader will find entries on subject matter covering: * disciplinary theory * legislation affecting the work of archaeologists * pre-excavation surveying * excavation methodology * on-site conservation techniques * post-excavation analysis The rapid evolution of analytical technology is often superficially treated or not covered at all in textbooks or other commonly available sources. Here, the latest refinements in techniques such as radiometric dating, stable isotopic analysis, and the PCR technique of DNA analysis are presented clearly and authoritatively. The discussion of these techniques is amplified by including results of the work of professionals conducting interdisciplinary research and by covering the methodologi enhancements provided by the physical and natural sciences. Cultural property legislation, regardless of its country of origin, has affected how archaeologists conduct their work. This encyclopedia covers all major U.S. legislation developed for the protection of cultural property, including the recent Native American Graves Protection and Repatriation Act, and offers a substantial article on worldwide legislation concerning the reburial of human remains and its effects on the present and future practice of archaeology. Without some sort of conservation program at the point of excavation, valuable materials may be inadvertently contaminated or destroyed. Many simple and low-cost techniques to promote both sample integrity and long-term preservation for major classes of materials are described in this volume. Traditional treatments of method and theory usually focus on prehistoric periods and are limited in their geographic range. This volume includes discussions based on various historical periods on different continents, as reflected in entries such as Historical Archaeology, Industrial Archaeology, Medieval Archaeology, and Classical Archaeology.